Development of Community-Based Peer-to-Peer Energy Trading Mechanism Using Z-Bus Network Cost Allocation - Noorfatima, Nadya; Choi, Yunjeong; Lee, Semi; Jung, Jaesung (Frontiers in Energy Research, 2022)
Community-based peer-to-peer (P2P) energy trading is applied to manage local market transactions to maximize the social welfare of the community. However, the increasing number of distributed energy resources in distribution systems affects the performance of community-operators in P2P energy trading. Hence, this study develops a community-based P2P energy trading mechanism to ensure fair profit allocation and reduce computation cost, even with numerous participants. To achieve this, the P2P participants were aggregated into smaller groups using the K-means clustering method, allowing the community manager to perform market transactions in a hierarchical manner. In the hierarchical P2P market, social welfare maximization is performed in the higher layer and profit distribution in the lower layer. Furthermore, the Z-bus network cost allocation method was applied to determine the network usage cost and was thus considered as a parameter to ensure fair profit allocation based on the Shapley value. The proposed method was simulated in South Korean P2P energy trading at various market scales. The results showed an improvement in the proposed method compared with conventional single-layer community-based P2P energy trading.